NILAI NILAI PENDIDIKAN KARAKTER KH. AHMAD DAHLAN DALAM MENINGKATKAN KECERDASAN SPIRITUAL DAN SOSIAL SISWA DI SMK MUHAMMADIYAH JEMBER - Ilham Aziz Suharto; Hairul Huda; Sofyan Rofi (PGMI Department of Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia, 2023)
Education and character have great contact because the two are interdependent. There is some news regarding the waning value of character education in students, therefore the need for good character education. the focus of this research is (1) How are the values ​​of Kh. Ahmad dahlan in improving the Spiritual Intelligence of Jember Muhammadiyah Vocational High School students? (2) What are the Values ​​of Character Education Kh. Ahmad dahlan in improving the Social Intelligence of Jember Muhammadiyah Vocational High School students?. This study used a qualitative-descriptive approach at SMK Muhammadiyah Jember. Data collection procedures used observation, interviews, documentation with a total of 5 technical informants. The analysis included data categorization, data reduction, data presentation and conclusion drawing. As well as data validity using credibility. The results obtained from this study are (1) There is a Habituation of Character Education Values ​​Kh. Ahmad dahlan in improving the Spiritual Intelligence of students at SMK Muhammadiyah Jember Namely Religiosity namely Dhuha Prayer, Nationalism namely Commemorating Religious Holidays, Honest namely IstiqomahDuha prayer, Integrity namely Consistent upholding noble values. (2) There is habituation of Kh Character Education Values. Ahmad dahlan in improving the Spiritual Intelligence of students at the Muhammadiyah Jember Vocational School, namely Religiosity, namely Praying for sick friends, Nationalism, namely participating in the flag ceremony, Honest, namely Students not smoke at Integrity schools, namely Students wearing complete uniforms.